A phase I-II trial of autologous peripheral blood stem cell transplantation in the treatment of refractory autoimmune disease. Issue 4 (26th August 2005) - Tsukamoto, H; Nagafuji, K; Horiuchi, T; Miyamoto, T; Aoki, K; Takase, K; Henzan, H; Himeji, D; Koyama, T; Miyake, K; Inoue, Y; Nakashima, H; et al.
Abstract : Objectives: To carry out a phase I-II trial to elucidate the feasibility and efficacy of high dose cyclophosphamide (CY) supported by autologous peripheral blood stem cell transplantation (PBSCT) in the treatment of severe and refractory autoimmune disease (AD). Methods: Peripheral blood stem cells (PBSCs) were mobilised during haematological recovery after relatively high dose CY (2 g/m 2 ) for 2 days, followed by administration of granulocyte colony stimulating factor. After collecting PBSCs—more than 2×10 6 CD34+ cells/kg—by apheresis, CD34+ cells were immunologically selected and cryopreserved. Eight patients were enrolled—five had systemic sclerosis (SSc) alone, one had SSc with systemic lupus erythematosus, one amyopathic dermatomyositis (ADM), and one Wegener's granulomatosis (WG). All of the patients were treated with high dose CY (50 mg/kg) for 4 days and autologous PBSCT. Results: Haematopoietic reconstitution was rapid and sustained. Toxicity due to the regimen included various infections such as pneumonia, sepsis, cystitis, herpes zoster, and acute heart failure. However, there was no treatment related mortality. Encouraging results were obtained after autologous PBSCT. Sclerosis of the skin was markedly improved in all of the patients with SSc. Interstitial pneumonia (IP), evaluated by Pao 2, serum KL-6 levels, and pulmonary high resolution computed tomography, improved significantly. In a patient with ADM, severe and progressive IP also improved markedly. In a patient with WG, the size of the left orbital granuloma decreased substantially, resulting in reduction of the exophthalmos. Conclusions: These observations suggest that high dose CY with autologous PBSCT is feasible and may be effective in the treatment of severe and refractory AD.